STRATEGI MANAJEMEN KEUANGAN YANG EFEKTIF UNTUK PENINGKATAN TARAF HIDUP MASYARAKAT - Teguh Prakoso; Rina Apriliani (JOURNAL OF COMMUNITY DEDICATION, 2024)
Effective financial management strategies for improving people's living standards refer to a series of planned approaches and methods in managing financial resources, both at the individual, family, and community levels, which aim to improve economic well-being and overall quality of life. These strategies include careful financial planning, wise management of income and expenditure, optimal use of financial instruments and investments, and increased financial literacy, which collectively aim to create financial stability, economic growth, and improve people's living standards in the long term. The study method in this study uses the literature method. The results of the study show that strategies such as careful budget planning, wise debt management, investment diversification, and increased financial literacy have a significant positive impact on financial stability and economic growth of the community. This study also identifies challenges in implementing these strategies, including gaps in knowledge and access to financial services. In conclusion, the implementation of effective financial management strategies, supported by appropriate policies and continuous education, can be a key instrument in improving people's living standards and encouraging inclusive economic development.